Chemical Heterogeneity of Mg, Mn, Na, S, and Sr in Benthic Foraminiferal Calcite - van Dijk, Inge; Mouret, Aurélia; Cotte, Marine; Le Houedec, Sandrine; Oron, S.; Reichart, Gert-Jan; Reyes-Herrera, Juan; Filipsson, Helena L.; Barras, Christine (Frontiers in Earth Science, 2019)
The chemical composition of fossil foraminiferal shells (tests) is widely used as tracers for past ocean chemistry. It is therefore important to understand how different (trace-)elements are transported and incorporated into these tests from adjacent seawater. The elemental distribution within the walls of foraminiferal tests might be used to differentiate between proposed transport mechanisms. Here, the micro-distribution of Mg, Mn, Na, S and Sr in tests of three species of foraminifera, known to have contrasting test chemistry, is investigated by a combination of EPMA, NanoSIMS, µXRF and µXANES analyses. The three investigated species are the symbiont-barren Ammonia sp. T6 and Bulimina marginata, which precipitate a low-Mg calcite test, and the symbiont-bearing species Amphistegina lessonii, which produces a test with intermediate Mg content. Because all analysed tests were formed under controlled and identical laboratory conditions, the observed distributions of elements are not due to environmental variability, but are a direct consequence of the processes involved in calcification or, in the case of Amphistegina lessonii, possibly symbiont activity. Despite some variability in elemental micro-distribution between specimens from a given species, our combined dataset shows species-specific distributions of the elements (e.g., peak heights and/or band-widths), but also a systematic co-location of Mg, Na, S and Sr for all three species, suggesting a coupled or simultaneous uptake, transport, and incorporation of these elements during chamber addition. The observed trace-element patterns generally reflect a laminar calcification model, suggesting that heterogeneity of these elements is intrinsically linked to chamber addition. Although the incorporation of redox-sensitive Mn depends on the Mn-concentration of the culture medium, the Mn distribution observed in Ammonia sp. suggests that Mn transport is similarly linked to laminar calcification dynamics. However, for B. marginata, Mn banding was sometimes anti-correlated with Mg banding, suggesting that (bio)availability, uptake and/or transport of Mn differs from Ammonia sp. Our results from symbiont-bearing A. lessonii suggest that the activity of symbionts (i.e., photosynthesis/respiration) may influence the incorporation of Mn due to alternation of the chemistry in the microenvironment of the foraminifera, an important consideration in the development of this potential proxy for past oxygenation of the oceans.